Artificial Intelligence as a Catalyst for Innovation in Early Childhood Pedagogy: A Critical Review - Tyasa Safa Amelia (Lia Center of Research and Education, 2025)
The integration of artificial intelligence technologies in early childhood education represents a significant paradigm shift in pedagogical practices, yet comprehensive critical analyses of AI's role as an innovation catalyst remain limited. This systematic literature review aims to synthesize recent research examining AI-driven innovations in early childhood pedagogy, identifying key trends, opportunities, and challenges for children aged 0-8 years. Following PRISMA guidelines, a comprehensive search across multiple databases yielded 34 high-quality studies published between 2019-2024. Data extraction employed a structured coding framework examining AI technology types, pedagogical applications, theoretical alignments, and ethical considerations. Results revealed four primary AI technology categories: intelligent tutoring systems (41.2%), educational robotics (35.3%), natural language processing (17.6%), and computer vision systems (5.9%). Educational robotics demonstrated the highest learning outcome improvements (42%), followed by intelligent tutoring systems (35%). AI technologies successfully enhanced personalized learning delivery, social-emotional development, and STEM skill acquisition while maintaining alignment with constructivist and play-based learning principles. However, significant challenges emerged regarding data privacy, algorithmic bias, teacher professional development requirements, and digital equity concerns. The findings indicate that while AI serves as a powerful catalyst for pedagogical innovation, successful implementation requires intentional approaches prioritizing developmental appropriateness, ethical considerations, and equitable access to ensure AI enhances rather than replaces essential human elements in early learning environments.